Evaluation of Tc-99m Tetrofosmin Scan for Coronary Artery Disease Diagnosis - Ghanem, Georges (2002)
Detection of myocardial perfusion abnormalities using Tc-99m tetrofosmin was evaluated for sensitivity and specificity compared to coronary angiography. Between January 1996 and January 1998, exercise stress tests and myocardial scintigraphy were performed in 58 patients, followed by coronary angiography within 2 months. There were 48 males and 10 females, aged 33 to 72 years (mean, 57 years). The sensitivity and specificity of exercise stress tests were 64% and 68%, respectively, while the sensitivity and specificity of Tc-99m tetrofosmin scans were 88% and 75%, respectively, compared to angiography. For Tc-99m tetrofosmin scans, the sensitivity was 78% for the left anterior descending artery, 66% for the left circumflex artery, and 76% for the right coronary artery; specificity was 74% for the left anterior descending artery, 90% for the left circumflex artery, and 75% for the right coronary artery. It was concluded that Tc-99m tetrofosmin allowed high-quality myocardial perfusion imaging with results comparable to those obtained using thallium-201 chloride.